Improving Healthcare Worker Resilience and Well-Being During COVID-19 Using a Self-Directed E-Learning Intervention - Kelly, Frances; Uys, Margot; Bezuidenhout, Dana; Mullane, Sarah L.; Bristol, Caitlin (Frontiers in Psychology, 2021)
Introduction: High rates of burnout, depression, anxiety, and insomnia in healthcare workers responding to the COVID-19 pandemic have been reported globally. Methods: Responding to the crisis, the Foundation for Professional Development (FPD) developed an e-learning course to support healthcare worker well-being and resilience. A self-paced, asynchronous learning model was used as the training intervention. Each module included practical, skill-building activities. An outcome evaluation was conducted to determine if completing the course improved healthcare worker knowledge of and confidence in the learning outcomes of the course, their use of resilience-building behaviours, their resilience, and their well-being. A secondary objective was to explore if there were any associations between behaviours, resilience, and well-being. Participants completed pre- and post-course questionnaires to measure knowledge of and confidence in the learning outcomes, y, frequency of self-reported resilience-building behaviours, and levels of resilience (CD-RISC) and well-being (WHO-5). Results were analysed in STATA using paired T-tests, univariate and multivariate linear regression models. Results: Participants (n = 474; 77.6% female; 55.7% primary care) exhibited significant increases in knowledge, confidence, resilience-building behaviour, resilience, and well-being scores. Statistically significant improvements in the frequency of resilience-building behaviours led to significant improvements in resilience (0.25 points; 95% CI: 0.06, 0.43) and well-being (0.21 points; 95% CI: 0.05, 0.36). Increasing changes in well-being scores had a positive effect on change in resilience scores (β = 0.20; 95% CI: 0.11, 0.29), and vice versa (β = 0.28; 95% CI: 0.14, 0.41). Conclusion: A healthcare worker e-learning course can build knowledge and skills that may prompt changes in resilience-building behaviours and improvements in well-being and resilience scores. The findings suggest that e-learning courses may improve more than competency-based outcomes alone but further research is warranted to further explore these relationships.